(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we consider the Cauchy problem of the axially symmetric tropical climate model with fractional dissipation. By using the energy method, we establish a new regularity criteria for the axisymmetric solutions of the 3D Tropical climate model without swirl.